Biological Activity of Extracts from Differently Produced Blueberry Fruits in Inhibiting Proliferation and Inducing Apoptosis of HT-29 Cells - Ewelina Kiernozek; Piotr Maslak; Ewa Kozlowska; Ingeborga Jarzyna; Dominika Średnicka-Tober; Ewelina Hallmann; Renata Kazimierczak; Nadzieja Drela; Ewa Rembiałkowska (Foods, 2022)
For several decades, people have been searching for natural substances of plant origin that, when introduced into the diet, could strengthen immunity, have anticancer properties, and support conventional therapy. The development of agriculture with the implementation of various plant cultivation systems, apart from the economic aspect, results in the search for such cultivation conditions that would contribute to obtaining the most beneficial product for health. Therefore, the aim of our research is as follows: (a) to compare the antiproliferative activity and the ability to induce apoptosis of HT-29 cells by extracts from blueberry fruits deriving from different types of cultivation systems (conventional, organic, and biodynamic); (b) to examine whether the interaction of extracts with anticancer drugs used in the treatment of colorectal cancer is influenced by the type of cultivation, and (c) to investigate whether extracts obtained from fruits from subsequent years of cultivation retain the same biological activity. The results of our study are promising but inconclusive. A statistically significant difference occurred in only one of the two years of the study. The greatest inhibition of proliferation is observed for biodynamic cultivation compared to organic cultivation, while the highest levels of apoptosis and necrosis of HT-29 cells are induced by blueberry fruit extracts obtained from organic cultivation. The complementary effect of the extracts on the inhibition of HT-29 cell proliferation by anticancer drugs (5-FU and Erbitux) is not demonstrated. The induction of apoptosis by 5-FU is not enhanced by blueberry extracts, in contrast to necrosis. The level of apoptosis and necrosis induced by Erbitux is potentiated, but no dependence on crop type is shown. Blueberry fruit extracts from two consecutive years of cultivation did not maintain the same activity. A plausible reason for the variability in the composition and biological activity of fruit extracts obtained from two years of cultivation is the varying environmental conditions.